Quantifying transnational corruption: a comprehensive approach of Odebrecht and Siemens scandals in international relations - Campos, Tales de Paula Roberto de (2025)
Corruption, a persistent facet of human nature, still prowls the globalized world. Essentially, corruption means the unlawful appropriation of public resources for private gains. Therefore, understanding its global impact requires in-depth research into transnational corruption within the field of International Relations. This thesis aims to investigate the key determinants underpinning transnational corruption schemes, focusing on the Odebrecht case (2000-2016) and the Siemens corruption scandal (1999-2012). The methodology combines qualitative and quantitative approaches to investigate the statistical results allied with the companies analysis. The qualitative part explores the mechanisms that facilitated Odebrecht and Siemens to sustain the development of financial crimes such as bribes, embezzlement, money laundering, and other related felonies. The quantitative aspect involves an extensive statistical database encompassing 365 records, predominantly documenting illegal operations orchestrated by both companies. This database includes crucial variables such as contract values, company revenues, bribe amounts, foreign direct investment figures, and transparency indices. It is a valuable resource for the comprehensive analysis of these corruption cases, shedding light on their multifaceted dimensions and global repercussions. By merging qualitative insights with quantitative data, this research seeks to contribute to the studies related to the transnational corruption impact in International Relations, proposing a more nuanced comprehension of its pervasive influence on the global stage.